ARTIFICIAL INTELLIGENCE AS A MEANS TO ENHANCE SPEAKING COMPETENCE: PEDAGOGICAL OR TREND? - Maria Asumpta Deny Kusumaningrum; Christina Atika Yulina (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Oral proficiency in Aviation English is essential for operational safety; however, speaking instruction in aviation programs is often constrained by limited time, large classes, and learner anxiety, resulting in reduced opportunities for practice and feedback. This study examined the role of Artificial Intelligence (AI) as a pedagogical solution to enhance Aviation English speaking skills. Employing a mixed-methods quasi-experimental pretest–posttest control group design, the study involved first-semester students of the Aerospace Engineering Study Program at Institut Teknologi Dirgantara Adisutjipto enrolled in Bahasa Inggris Teknik I. A total of 90 students were assigned to an experimental group (n = 49) and a control group (n = 41). Both groups received identical classroom instruction; however, the experimental group practiced scenario-based aviation dialogues using AI with automatic speech recognition and immediate feedback, while the control group engaged in conventional role-plays. Data were collected through speaking performance tests, perception questionnaires, AI learning logs, and semi-structured interviews. Results indicated equivalent baseline proficiency, but significantly greater speaking gains in the experimental group (M = +9.6 vs. +3.4; p < .001; d = 0.85), particularly in pronunciation and fluency. These findings confirm that AI-assisted practice effectively enhances Aviation English speaking when integrated with authentic tasks and guided instructor support. ABSTRAK Kemahiran lisan dalam Bahasa Inggris Penerbangan sangat penting bagi keselamatan operasional, tetapi pembelajaran berbicara dalam program penerbangan sering terkendala keterbatasan waktu, kelas besar, dan kecemasan belajar, sehingga kesempatan praktik dan umpan balik menjadi terbatas. Penelitian ini mengkaji peran Kecerdasan Buatan (Artificial Intelligence / AI) sebagai solusi pedagogis untuk meningkatkan kemampuan berbicara Bahasa Inggris Penerbangan. Penelitian menggunakan metode campuran dengan desain kuasi-eksperimen pretest–posttest control group dan melibatkan mahasiswa semester pertama Program Studi Teknik Dirgantara Institut Teknologi Dirgantara Adisutjipto yang mengikuti mata kuliah Bahasa Inggris Teknik I. Sebanyak 90 mahasiswa dibagi ke dalam kelompok eksperimen (n = 49) dan kelompok kontrol (n = 41). Kedua kelompok memperoleh pembelajaran yang sama; namun, kelompok eksperimen berlatih dialog penerbangan berbasis skenario menggunakan AI dengan pengenalan ujaran otomatis dan umpan balik langsung, sedangkan kelompok kontrol melakukan role-play konvensional. Data dikumpulkan melalui tes kinerja berbicara, kuesioner persepsi, log pembelajaran AI, dan wawancara semi-terstruktur. Hasil menunjukkan kemampuan awal yang setara, tetapi peningkatan kemampuan berbicara kelompok eksperimen secara signifikan lebih tinggi (M = +9,6 vs. +3,4; p < 0,001; d = 0,85), khususnya pada aspek pelafalan dan kefasihan. Temuan ini menegaskan bahwa praktik berbantuan AI efektif meningkatkan kemampuan berbicara Bahasa Inggris Penerbangan apabila dipadukan dengan tugas autentik dan bimbingan dosen.